Persulfate-assisted anaerobic digestion systems: advances in microbial electron transport chain reconstruction and metabolic regulation driven by reactive oxygen species - Yingjin Song; Sheng Xu; Yanshan Wang; Lan Mu; Huiling Niu; Qingyi Li; Yinjie Zhong; Yvxing Luo; Zhi Wang; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

Boron-mediated pectin demethylesterification improves Na+ retention in root cell wall and alleviates salt stress in Brassica napus L. - Yu Yang; Wenjing Hao; Rui Jing; Xiaolei Feng; Diqing Yin; Muhammad Riaz; Mu Lu; Yusheng Niu; Lei Yan (Plant Science, 2026)

Integrating scale-matched spatial scales into water scarcity risk screening in China - Jiayu Zhang; Dedi Liu; Jiabo Yin; Feng Yue; Jiaoyang Wang; Zhenyu Mu; Hanxu Liang; Zhilin Niu; Zhengbo Peng (Journal of Hydrology, 2026)

Study on the mechanism of selective flotation separation of fine coal and kaolinite enhanced by environmentally friendly small-molecule carboxylic acids - Wei Xiao; Yuping Fan; Xiaomin Ma; Jian Niu; Maoqing Yang; Xianshu Dong; Yuanpeng Fu; Zeyu Feng; Pengcheng Wen; Yanze Mu (Minerals Engineering, 2026)

Nanocarbon catalyzed ethylbenzene oxidative dehydrogenation: Intrinsic activity enhancement via electronic structure modulation with transition metals - Xueya Dai; Miao Guo; Kunru Fan; Ruobing Chen; Mu Niu; Zhifeng Gao; Wei Qi (Chemical Engineering Journal, 2026)

Wave climate characteristics and long-term trends in the northern South China Sea: A 31-year hindcast study for offshore engineering applications - Jinzong Guan; Qianru Niu; Yanqing Feng; Yan Li; Xiaomei Liao; Lin Mu (Ocean Engineering, 2026)

Nitric acid-modified co-pyrolyzed biochar from gentamicin mycelial residue and biomass regulates cattle manure composting: Reducing carbon loss and enhancing humification - Yingjin Song; Huiling Niu; Yamei Zeng; Guanyi Chen; Zeng Dan; Beibei Yan; Lan Mu; Yuxing Luo; Yinjie Zhong; Sheng Xu; Qingyi Li; Anna Jin (Journal of Environmental Management, 2026)

Collaborative Optimization of Capacity and Operation Strategy for an Air-Source and Ground-Source Heat Pump Coupled Heating System - Huan Liu; Junqing Liu; Peng Li; Yanru Lu; Xiaojie Niu; Jinghui Luo; Yongchao Mu (Applied Geophysics, 2026)

Comparison of nitrogen oxides (NO, NO2) analyzers from controlled conditions in a 100 m3 outdoor simulation chamber to field observations - Xuanming Huang; Xiaowei He; Jinzhao Tong; Baobin Han; Shichuan Ni; Zhiwei He; Xuelian Zhong; Xinmiao Xu; Min Cai; Yang Wang; Chenyang Xue; Wenya Niu; et al. (Journal of Environmental Sciences, 2026)

Transition conditions between seepage-induced and buoyancy-induced reservoir landslides: Insights from sensitivity analysis on reservoir landslide stability - Zongxing Zou; Yikai Niu; Luoxia Li; Rui Mu; Liangqing Wang; Haojie Duan (Engineering Geology, 2026)

Dietary optimal arginine content of juvenile mud crab Scylla paramamosain and its roles in growth promotion and immune defense - Qiang Li; Zhennan Wang; Ye Sun; Mingming Niu; Ce Shi; Herve Migaud; Changkao Mu; Chunlin Wang; Yangfang Ye (Marine Life Science & Technology, 2026)

Grass carp pyruvate kinase PKM acts as a key viral helper by orchestrating NS80-mediated VIB formation and multifaceted inhibition of the RLR-IFN-STAT1 antiviral cascade - Mu Niu Yang; Yang Chen; Ming Xian Chang (Fish & Shellfish Immunology, 2026)

Intercalation-mediated bionic nano-hydrogel adhesives for robust omni-domain adhesion - Jialve Sun; Zhengzhi Mu; Tianye Yang; Hexuan Yu; Wenda Song; Zhiyan Zhang; Junqiu Zhang; Shichao Niu; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

A Deep Learning–Based Bias Correction Model for Tropical Cyclone Track and Intensity towards Forecasting of the TianXing Large Weather Model - Shijin Yuan; Xingzhou Wang; Bin Mu; Guansong Wang; Zeyi Niu; Hao Li (Advances in Atmospheric Sciences, 2026)

Joint topic entity and intent recognition model for multimodal agricultural diseases and pests question answering - Jingzhong Huang; Xia Hao; Yu Wang; Ruizhi Song; Zenan Mu; Sijie Niu; Xuchao Guo (Computers and Electronics in Agriculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Role of flow electrode chamber channel depth in charge transfer and ion migration in FCDI: Mechanistic insights and energy efficiency evaluation - Cheng Wang; Jianrui Niu; Situ Mu; Yongkun Shi; Jing Zhang; Chun Liu; Junjun Ma (Chemical Engineering Journal, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

Redox electrolyte enhances dual-anode FCDI (DA-FCDI) desalination of brackish and synchronously removal NOM - Kexin Kang; Situ Mu; Jianrui Niu; Yongkun Shi; Jing Zhang; Chun Liu; Junjun Ma (Chemical Engineering Journal, 2026)

Excavation instability with end restraint effect under high stress: insights from True-Triaxial simulation experiments - Ting Zhang; Si-Qiao Wang; Shi-Hong Wu; Mu-Qing Su; Jian-Zhi Zhang; Yong Niu (Bulletin of Engineering Geology and the Environment, 2026)

MASS-LSVD: A Large-Scale First-View Dataset for Marine Vessel Detection - Yunsheng Fan; Dongjie Ju; Bing Han; Feng Sun; Liran Shen; Zongjiang Gao; Dongdong Mu; Longhui Niu (Journal of Marine Science and Engineering, 2025)
In this paper, we release a new large-scale dataset containing multiple categories of ships and floating objects at sea, which we call MASS-LSVD. It is used to train and validate target detection algorithms and future large models for ship autopiloting. The dataset was captured by a visible light camera installed aboard the world’s first intelligent research, teaching, and training ship, “Xinhongzhuan”. This MASS (maritime autonomous surface ship) was operated by Dalian Maritime University, China. We have collected more than 4000 h of video of the “Xinhongzhuan” vessel’s voyage in the Bohai Sea and other areas, which are carefully classified and filtered to cover as much as possible the various types of sample data in the marine environment, such as light intensity, weather, hull shading, data from ocean-going voyages, entering and exiting ports, etc. The dataset contains 64,263 1K-resolution images captured from video footage, covering four main ship types: Fishing Boat, Bulk Carrier, Cruise Ship, Container ship, and an ‘Other Ships’ class, for vessels that cannot be specifically classified. The dataset currently contains 64,263 pairs of 1K-resolution images covering four common ship types (fishing boat, bulk carrier, cruise ship, container, and other ship, where no specific ship type can be determined). All the images have been labeled with high-precision manual bounding boxes. In this paper, the MASS-LSVD dataset is used as the basis for training various target detection algorithms and comparing them with other datasets, which compensates for the lack of first-view images in the vessel target detection dataset, and MASS-LSVD is expected to be used to facilitate the research and application of autonomous ship navigation models in the framework of computer vision.

Hypothermal effects of cold anesthesia on the vitality and muscle quality of live Chinese mitten crab (Eriocheir sinensis) - Laixin Chen; Yanchao Han; Honglei Mu; Ben Niu; Ruiling Liu; Guannan Wang; Huizhi Chen; Lishu Wang; Hangjun Chen; Haiyan Gao (Food Research International, 2025)

Utilizing air discharge to preserve post-harvest quality of lotus root by suppressing fusarium oxysporum - Pengyue Zhang; Huizhi Chen; Ben Niu; Honglei Mu; Ruiling Liu; Yanchao Han; Ming Yin; Chaoyi Shen; Haiyan Gao; Hangjun Chen (Food Chemistry, 2025)

Comprehensive assessment of full-cycle high-solid anaerobic digestion of straw for methane production update: Focus on performance improvement and circular economy - Yingjin Song; Yinjie Zhong; Yanshan Wang; Lan Mu; Yuxing Luo; Sheng Xu; Huiling Niu; Zhi Wang; Beibei Yan; Guanyi Chen (Environmental Research, 2025)

Analysis and optimization of a quasi-zero-stiffness vibration isolator based on partially rigidized compliant mechanisms - Zhi-Qiang Zhang; Mu-Qing Niu; Li-Qun Chen (Engineering Structures, 2025)

Plasmonic metamaterials with closed cells for infrared/visible compatible stealth - Zhiyu Ren; Tong Zhao; Sijia Niu; Wencheng Chen; Xiaoming Liu; Wangzhong Mu; Tie Liu; Qiang Wang (Chemical Engineering Journal, 2025)

Hourly photosynthetically active radiation prediction in solar greenhouses using Bayesian optimized machine learning and deep learning based on limited local weather data - Menglong Wu; Ruoyu Li; Chang Lv; Aihong Dong; Fei Mu; Wenquan Niu (Computers and Electronics in Agriculture, 2025)

Spatiotemporal dynamics of retrogressive thaw slumps on the Qinghai-Tibet Plateau: integrating UAV-LiDAR and GPR - Fan Yu; Jing Luo; Fujun Niu; Zhanju Lin; Bingyan Li; Yanhu Mu; Xin Ju; Minghao Liu; Guoan Yin; Zeyong Gao; Xiaolong Zhao; Chengming Zhang (Landslides, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Salicylic acid nanoliposomes treatment alleviates chilling injury in postharvest baby ginger by regulating membrane lipid metabolism - Zhenzhen Mi; Honglei Mu; Yanchao Han; Ruiling Liu; Ben Niu; Guannan Wang; Huizhi Chen; Haiyan Gao; Hangjun Chen (Food Chemistry, 2025)

Comprehensive analysis of single tube falling film heat transfer performance considering dynamic growth of fouling - Boyu Wang; Yuzhe Niu; Di Wang; Xingsen Mu; Yali Guo; Shengqiang Shen (Desalination, 2025)

Boron-induced phenylpropanoid metabolism, Na+/K+ homeostasis and antioxidant defense mechanisms in salt-stressed soybean seedlings - Mu Lu; Muhammad Riaz; Kaiqing Tong; Wenjing Hao; Yu Yang; Xiaomeng Zhao; Lu Wang; Yusheng Niu; Lei Yan (Journal of Hazardous Materials, 2025)

Sustained antimicrobial polymer film from γ-CD-MOF humidity switch for fruit and vegetable preservation - Wangfei Yu; Guannan Wang; Huizhi Chen; Honglei Mu; Ben Niu; Yanchao Han; Lishu Wang; Hangjun Chen; Haiyan Gao (Food Chemistry, 2025)

Development of cushioning-antibacterial dual-functional cellulose packaging and its application for the Chinese bayberry during simulated transportation vibration - Yifan Xue; Ben Niu; Yanchao Han; Weijie Wu; Guannan Wang; Ming Yin; Xiangjun Fang; Ruiling Liu; Hangjun Chen; Haiyan Gao; Honglei Mu (Food Packaging and Shelf Life, 2025)

Association Between Mixed Metal Exposures and Female Infertility: A Large Cross-sectional Study - Yunan He; Xiaoxiao Su; Zhiping Niu; Bolun Zhang; Hui Mu; Lu Wang; Yuanqing Yao; Xiaohong Wang (International Journal of Environmental Research, 2025)

Sustainable Fe(II) oxidation/reduction and release/recovery dual cycle in a multi-chamber Fe(III)/Peroxymonosulfate electrochemical system: Application, mechanism, and optimization - Minghao Yu; Meng Chen; Chenxu Yang; Jianrui Niu; Jing Zhang; Situ Mu; Ruina Zhang; Junjun Ma; Chun Liu (Chemical Engineering Journal, 2025)

Corrigendum to “Saline-alkaline stress induced metabolomic changes and survival recovery by trimethylamine N-oxide in the mud crab (Scylla paramamosain)” [Aquaculture Volume 599, 15 April 2025, 742,097]. - Mingming Niu; Huan Wang; Ce Shi; Changkao Mu; Chunlin Wang; Yangfang Ye (Aquaculture, 2025)

Saline-alkaline stress induced metabolomic changes and survival recovery by trimethylamine N-oxide in the mud crab (Scylla paramamosain) - Mingming Niu; Huan Wang; Ce Shi; Changkao Mu; Chunlin Wang; Yangfang Ye (Aquaculture, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

Machine learning-assisted structure design and materials screening of a bilayer thin-film selective thermal emitter for infrared stealth technology - Sijia Niu; Zhiyu Ren; Chenchong Wang; Xiaoming Liu; Wangzhong Mu; Qiang Wang (Chemical Engineering Journal, 2025)

Astaxanthin ameliorates high-carbohydrate diet-induced ER stress, immunosuppression and hepatic glucose metabolism through AMPK/autophagy pathway in Channa argus - Mu-Yang Li; Yun-Zhuo Liu; Xiu-Mei Chen; Xiao-Tian Niu; Lu Chen; Lei Zhao; Gui-Qin Wang (Aquaculture, 2025)

Intelligent veins recognition method for slope rock mass geological images in complex background noise - Niu Wen-jing; Chen Yuan-xin; He Ben-guo; Chen Guang-mu; Qiu Zhen-hua; Fan Wen-yu (Computers & Geosciences, 2025)

Enhanced electrochemical performance of NCM811-based batteries by using a multifunctional electrolyte additive - Aijia Wei; Shuxing Mei; Jinping Mu; Peng Liu; Xue Bai; Rui He; Xiaohui Li; Yuxin Niu; Lihui Zhang; Zhenfa Liu; Lei Wang (Chemical Engineering Journal, 2025)

Investigating the metabolism of four sulfonamides in grass carp via HPLC-MS for screening candidate materials of matrix reference material - Chaoying Zhang; Bingjie Niu; Jianhui Fang; Yingchun Mu; Jincheng Li; Huan Liu (Food Chemistry, 2025)

Efficient image inpainting of microresistivity logs: A DDPM-based pseudo-labeling approach with FPEM-GAN - Zhaoyan Zhong; Liguo Niu; Xintao Mu; Xin Wang (Computers & Geosciences, 2025)

Platinum nanoparticles confined in Zn-S-1 for efficient propane dehydrogenation - Shuwang Li; Lei Wang; Mu Niu; Junbiao Wu; Yide Han; Yan Xu; Jianhua Zhu; Zhuopeng Wang (Chemical Engineering Journal, 2025)

Dietary supplementation of Roseovarius litoreus improves survival and immune defense of the swimming crab Portunus trituberculatus - Mingming Niu; Weichuan Lin; Qingyang Wu; Ce Shi; Changkao Mu; Chunlin Wang; Yangfang Ye (Aquaculture, 2025)

Shiitake mushroom-derived extracellular nanovesicles: Preparation, characterization, and inhibition of Caco-2 cells - Xueli Yang; Zihao Zong; Ben Niu; Hangjun Chen; Weijie Wu; Xiangjun Fang; Ruiling Liu; Haiyan Gao; Honglei Mu (Food Chemistry, 2025)

High UV-shielding polyvinyl alcohol/chitosan-based transparent bioplastic film for food preservation - Mei Bao; Honglei Mu; Ben Niu; Ruiling Liu; Huizhi Chen; Hangjun Chen; Lishu Wang; Yanchao Han; Guannan Wang; Haiyan Gao (Food Packaging and Shelf Life, 2025)

A compliant helical structure to amplify inertia for nonlinear vibration absorption - Jun-Jie Huang; Mu-Qing Niu; Yimin Fan; Li-Qun Chen (Engineering Structures, 2025)

Lycorine hydrochloride interferes with energy metabolism to inhibit chemoresistant glioblastoma multiforme cell growth through suppressing PDK3 - Qingsheng Dong; Wanxiang Niu; Maolin Mu; Chengkun Ye; Pengfei Wu; Shanshan Hu; Chaoshi Niu (Molecular and Cellular Biochemistry, 2025)

Regionally adapted conservation tillage reduces the risk of crop yield losses: A global meta-analysis - Jun Sun; Wenquan Niu; Yadan Du; Li Ma; Siying Huang; Fei Mu; Qian Zhang; Guochun Li; Jinjin Zhu; Kadambot H.M. Siddique (Soil and Tillage Research, 2024)

The performance of a 100 m3 outdoor atmospheric simulation chamber in China - Yangang Ren; Jinhe Wang; Wenya Niu; Yang Jiao; Chenglong Zhang; Ravi Yadav; Yonghong Wang; Junfeng Liu; Chunshan Liu; Yujing Mu; Hong He (Science of The Total Environment, 2024)

N-doped carbon achieved by pyrolyzing urea and active carbon for the capacitive deionization coupled PMS oxidation system - Meng Chen; Chenxu Yang; Minghao Yu; Mengyao Han; Zihan Meng; Tian Zhao; Jianrui Niu; Situ Mu; Jing Zhang; Junjun Ma; Chun Liu (Desalination, 2024)

Multi-chamber membrane capacitive deionization coupled with peroxymonosulfate to achieve simultaneous removal of tetracycline and peroxymonosulfate reaction byproducts - Minghao Yu; Chenxu Yang; Meng Chen; Yunke Li; Kexin Kang; Cheng Wang; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Journal of Hazardous Materials, 2024)

Unraveling the chemosensory attributes of braised beef prepared from different regions using GC-MS combined with multivariate data analysis - Jie Sun; Mingyu Li; Xiaoqing Mu; Li Chen; Dequan Zhang; Fei Fang; Xiaoying Niu; Chunjiang Zhang (International Journal of Gastronomy and Food Science, 2024)

Examining starch metabolism in lotus roots (Nelumbo nucifera Gaertn.) during post-harvest storage at different temperatures - Xinxin Gong; Ruiling Liu; Yanchao Han; Ben Niu; Weijie Wu; Huizhi Chen; Xiangjun Fang; Honglei Mu; Haiyan Gao; Hangjun Chen (Food Chemistry, 2024)

Optimization of the intermediate chamber improves desalination performance in flow electrode capacitive deionization (FCDI): A comparative study - Yunke Li; Chenxu Yang; Meng Chen; Yonghuan Bian; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Desalination, 2024)

Exosomal circZNF800 Derived from Glioma Stem-like Cells Regulates Glioblastoma Tumorigenicity via the PIEZO1/Akt Axis - Ning Zhang; Pengfei Wu; Maolin Mu; Chaoshi Niu; Shanshan Hu (Molecular Neurobiology, 2024)
Exosomes play a crucial role in regulating crosstalk between tumor and tumor stem-like cells through their cargo molecules. Circular RNAs (circRNAs) have recently been demonstrated to be critical factors in tumorigenesis. This study focuses on the molecular mechanism by which circRNAs from glioma stem-like cell (GSLC) exosomes regulate glioblastoma (GBM) tumorigenicity. In this study, we validated that GSLC exosomes accelerated the malignant phenotype of GBM. Subsequently, we found that circZNF800 was highly expressed in GSLC exosomes and was negatively associated with GBM patients. CircZNF800 promoted GBM cell proliferation and migration and inhibited GBM cell apoptosis in vitro. Silencing circZNF800 could improve the GBM xenograft model survival rate. Mechanistic studies revealed that circZNF800 activated the PIEZO1/Akt signaling pathway by sponging miR-139-5p. CircZNF800 derived from GSLC exosomes promoted GBM cell tumorigenicity and predicted poor prognosis in GBM patients. CircZNF800 has the potential to serve as a promising target for further therapeutic exploration.

Microbicidal effect of negative air ion against Penicillium citrinum and quality control of Chinese bayberry - Guiren Yang; Ben Niu; Zihao Zong; Weijie Wu; Xiangjun Fang; Huizhi Chen; Yiqin Zhang; Honglei Mu; Haiyan Gao (Food Control, 2024)

Optimized tillage can enhance crop tolerance to extreme weather events: Evidence from field experiments and meta-analysis - Jun Sun; Wenquan Niu; Fei Mu; Ruoyu Li; Yadan Du; Li Ma; Qian Zhang; Guochun Li; Jinjin Zhu; Kadambot H.M. Siddique (Soil and Tillage Research, 2024)

A MYB transcription factor GhTT2 of Gossypium hirsutum regulates proanthocyanidin accumulation and improves osmotic tolerance in Arabidopsis - Jun Mei; Rongrong Mu; Qingqing Niu; Huimin Zhu; Ruoxi Chen; Xiaomiao Cai; Meng Miao; Dongliang Yu; Liping Ke; Yuqiang Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

The major role of glucocorticoid receptor (GR) in astaxanthin alleviates immune stress in Channa argus lymphocyte - Xiao-Tian Niu; Chuang Sun; Lei Zhao; Xiu-Mei Chen; Gui-Qin Wang; Mu-Yang Li (Aquaculture, 2024)

Changes in Sea Level along the South China Sea Coast Based on the Homogenized Tide Gauge Data - Yan Li; Lin Mu; Dawei You; Jiaying Wang; Qianru Niu; Xiaomei Liao (Journal of Marine Science and Engineering, 2024)
To estimate the changes in the annual mean sea level (MSL) and extreme sea levels (ESLs), the largest collection of tide gauge records from 10 tidal stations along the northern coast of the South China Sea (SCS) were analyzed in this study. Here, all the tide gauge records had been homogenized by a two-step process involving the detection of inhomogeneities, that is, breakpoints caused by non-climatic changes and the application of the adjustment. The study’s conclusions, based on the homogenized tide gauge records, can be summarized as follows: The instrument change and station relocation are the main causes for the identified inhomogeneities. From 1989 to 2018, the sea level along the SCS was at an average rate of 4.0 mm per year, as measured by the homogenized tide gauges. The ESLs from the nine tidal stations rose notably with interannual fluctuations, except for the XSA station. Additionally, the ESLs exhibited substantial decadal variations. The ESLs rose along the northern coast of the SCS and were accelerated at most stations throughout the whole study period, especially after the 1980s. There were significant positive correlations between the ESL and the annual MSL at most tide gauges. The MSL’s changes, especially long-term changes, play an important role in the change in ESLs.

The potential and prospects of modified biochar for comprehensive management of salt-affected soils and plants: A critical review - Guang Gao; Lei Yan; Kaiqing Tong; Hualong Yu; Mu Lu; Lu Wang; Yusheng Niu (Science of The Total Environment, 2024)

Characterization and fine mapping of a maize lesion mimic mutant (Les8) with enhanced resistance to Curvularia leaf spot and southern leaf blight - Jiankun Li; Tianyuan Fan; Ying Zhang; Ye Xing; Mengyao Chen; Ying Wang; Jie Gao; Na Zhang; Jinjun Tian; Chenyang Zhao; Sihan Zhen; Junjie Fu; et al. (Theoretical and Applied Genetics, 2024)

Record-breaking marine heatwave in northern Yellow Sea during summer 2018: Characteristics, drivers and ecological impact - Yan Li; Guoyu Ren; Qingyuan Wang; Lin Mu; Qianru Niu; Hanxiang Su (Science of The Total Environment, 2023)

Development of bio-based PLA/cellulose antibacterial packaging and its application for the storage of shiitake mushroom - Weitao Wang; Ben Niu; Ruiling Liu; Hangjun Chen; Xiangjun Fang; Weijie Wu; Guannan Wang; Haiyan Gao; Honglei Mu (Food Chemistry, 2023)

Analyzing the cellular and molecular atlas of ovarian mesenchymal cells provides a strategy against female reproductive aging - Longzhong Jia; Wenji Wang; Jing Liang; Shudong Niu; Yibo Wang; Jian Yang; Lingyu Li; Ge Wang; Xueqiang Xu; Lu Mu; Kaixin Cheng; Xuebing Yang; et al. (Science China Life Sciences, 2023)

Effect of oxyresveratrol on the quality and membrane lipid metabolism of shiitake mushroom (Lentinus edodes) during storage - Ben Niu; Yingchang Fei; Ruiling Liu; Hangjun Chen; Xiangjun Fang; Weijie Wu; Honglei Mu; Haiyan Gao (Food Chemistry, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Silibinin exerts neuroprotective effects against cerebral hypoxia/reoxygenation injury by activating the GAS6/Axl pathway - Weiping Li; Zhe Zhang; Jiawen Li; Jun Mu; Meng Sun; Xue Wu; Xiaochen Niu; Yang Yang; Huanle Yan; Xiaoling Xu; Chengxu Xue; Lu Qian; et al. (Toxicology, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

A seminal perspective on the role of chondroitin sulfate in biomineralization - Jia-xin Hao; Qian-qian Wan; Zhao Mu; Jun-ting Gu; Wei-wei Yu; Wen Qin; Yu-tao Li; Chen-yu Wang; Yu-xuan Ma; Kai Jiao; Franklin Tay; Lina Niu (Carbohydrate Polymers, 2023)

Analysis of Key Physiological Characteristics of Portunus trituberculatus in Response to Short-Term Low Salinity Stress - Xinni Zhang; Qi Liu; Jiali Wang; Gao Gao; Mingming Niu; Lizhi Chen; Huan Wang; Fangfang Wang; Chunlin Wang; Changkao Mu (Journal of Ocean University of China, 2023)

Circ_0008529 Contributes to Renal Tubular Cell Dysfunction in High Glucose Stress via miR-185-5p/SMAD2 Pathway in Diabetic Nephropathy - Zheli Niu; Guangwei Ren; Lijing Huang; Liqin Mu (Biochemical Genetics, 2023)

Response of intestinal microbiota to saline-alkaline water in mud crab (Scylla paramamosain) based on multiple low salinity culture modes - Mingming Niu; Xudong Li; Yuhao Chen; Kangxiang Qin; Guoling Liang; Yun Hu; Xiaosong Jiang; Huan Wang; Ritong Zhu; Chunlin Wang; Changkao Mu (Frontiers in Marine Science, 2023)
Introduction The intestinal microbiota acts as an additional “organ” that performs a variety of fu\nctions for the host’s health. However, the composition and role of the intestinal microbiota in Scylla paramamosain cultivated in inland low salinity saline-alkaline water are unknown. Methods Accordingly, from the perspective of practical production, we explored the intestinal microbiota communities and the critical bacteria of S. paramamosain in normal salinity seawater (NS), coastal low salinity seawater (CS), acute low salinity seawater (AS) and inland low salinity saline-alkaline water (IS). Results Results showed that there were significant differences in the diversity composition of intestinal microbiota and the relative abundance of dominant taxa in each group of cultured crabs. Firmicutes, Proteobacteria, Bacteroidota and Campilobacterota were shown to be the major phyla shared by the four groups, with Bacteroidota having the highest relative abundance (27.10%) in the inland low salinity saline-alkaline water group (IS). Fusobacteriota had the highest proportion in IS group compared with other low salinity groups. A total of 284 indicator bacteria were identified, belonging to eight phyla, and their relative abundances were varied significantly ( P < 0.05). Genus Carboxylicivirga , as the indicator bacterium of the IS group, may play a critical role in the adaptation of crab to saline-alkaline water environment. Moreover, salinity may exert considerable selective pressure on the entire microbial community. Discussion These findings revealed the features of the intestinal microbiome in S. paramamosain in multiple low salinity patterns, and provided candidate probiotics and basic information for crab farming in saline-alkaline water, which was conducive to the development and perfection of mud crab culturing technology in inland low salinity saline-alkaline water.

In vitro fermentation characteristics of the dietary fiber in bamboo (Phyllostachys edulis) shoots and its regulatory effects on the intestinal microbiota and metabolites - Weijie Wu; Qi Li; Hangjun Chen; Xiangjun Fang; Ben Niu; Ruiling Liu; Honglei Mu; Haiyan Gao (Food Chemistry, 2023)

Coupling coordination relationships between air pollutant concentrations and emissions in China - Qian Wu; Song Hong; Lu Yang; Hang Mu; Chaoqing Huang; Xiaoxiao Niu; Yanmei Zhong; Jiahui Yi; Chao He (Atmospheric Pollution Research, 2023)

Cryobacterium zhongshanensis sp. nov., an actinobacterium isolated from Antarctic soil - Guojiang Niu; Wenjing Wang; Hongmei Mu; Peiqiang Jiang; Xingtao Ren; Jing Li (Archives of Microbiology, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Multiple low salinity stress modes provided novel insight into the metabolic response of Scylla paramamosain adapting to inland saline-alkaline water - Mingming Niu; Gao Gao; Kangxiang Qin; Yuhao Chen; Huan Wang; Xing Li; Guoling Liang; Chunlin Wang; Changkao Mu; Qiong Su (Frontiers in Marine Science, 2022)
Scylla paramamosain is a high-quality cultivar for saline-alkaline water aquaculture as a euryhaline crustacean species. However, salinity impacts the respiratory metabolism, growth, and survival of marine crustaceans. The metabolic response of crabs adapting to multiple low salinity environments has not been thoroughly studied yet, especially in inland saline-alkaline water. In this study, we analyzed metabolites in the gill and hemolymph of crabs cultured in three different low salinity environments. The results showed that membrane composition (lipids and lipid molecules) and free amino acids played an essential role in the osmoregulation of crabs, and the energy consumption accompanied as well. Meanwhile, S. paramamosain relied on ion transport and energy metabolism under acute/short-term low salinity conditions for osmoregulation. In contrast, amino acids and energy metabolism occupied a leading position in long-term low salinity. Furthermore, taurine and hypotaurine play a vital role in crabs adapting to inland saline-alkaline water. This is the first study to identify the crucial metabolites and key pathways as biomarkers to differentiate the metabolic mechanisms of S. paramamosain under multiple low salinity stress modes based on GC-MS technology, which provided novel insight into the metabolic response of S. paramamosain adapting to inland low salinity saline-alkaline water, and provided theoretical guidance for the aquaculture of S. paramamosain in the inland saline-alkaline water.

Transcriptomic analysis of adaptive mechanisms in response to inland saline-alkaline water in the mud crab, Scylla paramamosain - Guoling Liang; Kangxiang Qin; Yuhao Chen; Mingming Niu; Huan Wang; Chunlin Wang; Changkao Mu; Lizhi Chen; Fangfang Wang; Qiong Su; Ritong Zhu (Frontiers in Marine Science, 2022)
Scylla paramamosain is an important marine aquaculture crustacean on the southeastern coast of China. Given the difficulties of overcrowded coastal aquaculture space and insufficient production, inland saline-alkaline water culture has the potential to alleviate this bottleneck. This study separated 600 crabs into four groups: normal salinity (12-18 ppt, NS), coastal low salinity (3-5 ppt, CS), inland low salinity saline-alkaline (1.5 ppt, IS), and acute low salinity (23 ppt down to 3 ppt, AS), followed by a transcriptomic analysis of the gills. CS-vs-NS, IS-vs-NS, and AS-vs-NS obtained 1154, 1012, and 707 DEGs, respectively. GO analysis showed that the DEGs of the three comparison groups were mainly involved in cellular process, metabolic process, biological regulation, organelle, membrane, extracellular region, binding, and catalytic activity. The findings demonstrate that a significant number of genes are engaged in controlling metabolic processes in the osmoregulation process, and that cell membrane catalysis and different enzymes play a vital part in the environmental adaption process. KEGG enrichment analysis revealed that IS possesses a considerable number of signaling pathways that play important roles in osmoregulation when compared to NS. The cAMP signaling pathway increased the expression of CaM and Na + /K + -ATPase. These findings show that cations like Ca 2+ , Na + , and K + are critical for S. paramamosain to adapt to inland low salinity saline-alkaline water, and that the cAMP signaling pathway regulates their levels. This research provides a theoretical foundation for improving the saline-alkaline aquaculture technology of S. paramamosain .

Metabolic Response in the Gill of Portunus trituberculatus Under Short-Term Low Salinity Stress Based on GC-MS Technique - Jiali Wang; Qi Liu; Xinni Zhang; Gao Gao; Mingming Niu; Huan Wang; Lizhi Chen; Chunlin Wang; Changkao Mu; Fangfang Wang (Frontiers in Marine Science, 2022)
Salinity is an important factor affecting the survival, growth, and metabolism of marine crustaceans. Low-salt stress will result in the death of swimming crabs. This paper investigates the metabolic response in the gills of Portunus trituberculatus under short-term low-salt stress by comparing the metabolic molecules in the four salinity treatment groups (24‰, 16‰, 12‰, and 8‰) by GC-MS technique. In this study, nine common differential metabolites such as pyruvate, malic acid, and phosphoethanolamine were found in the gill tissues of crabs. KEGG enrichment analysis revealed that six metabolic pathways, including the citric acid cycle, pyruvate metabolism, and the HIF-1 signaling system, were significantly impacted by low salt stimulation. According to the findings, salinity 12‰ is a critical node in crab adaptation to low salinity. In the process of adaptation to short-term low-salinity environment, amino acids participated in osmotic regulation, and organic acids such as pyruvate and malic acid were involved in energy metabolism to ensure their energy supply. This research further enriched the theory of osmotic regulation and metabolic mechanism of adaptation to low salt in crustaceans, with the goal of providing guidance for the improvement of culture technique in Portunus trituberculatus.

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

Effect of freeze-thaw cycles on uniaxial mechanical properties of cohesive coarse-grained soils - Yong-long Qu; Guo-liang Chen; Fu-jun Niu; Wan-kui Ni; Yan-hu Mu; Jing Luo (Journal of Mountain Science, 2019)

Effects of dietary Allium mongolicum Regel polysaccharide on growth, lipopolysaccharide-induced antioxidant responses and immune responses in Channa argus - Mu-Yang Li; Xin-Ming Zhu; Xiao-Tian Niu; Xiu-Mei Chen; Jia-Xin Tian; Yi-Di Kong; Dong-Ming Zhang; Lei Zhao; Gui-Qin Wang (Molecular Biology Reports, 2019)

A method for alpine wetland delineation and features of border: Zoigê Plateau, China - Yaomin Zheng; Zhenguo Niu; Peng Gong; Mengna Li; Lile Hu; Lei Wang; Yuxiang Yang; Haijun Gu; Jinrong Mu; Gejia Dou; Hui Xue; Lin Wang; et al. (Chinese Geographical Science, 2017)

Investigation on prenatal dengue infections in a dengue outbreak in Guangzhou City, China - Jie Yang; Jiawen Zhang; Qundi Deng; Junping Wang; Yunbin Chen; Xiaohong Liu; Fei Wu; Jianmin Niu; Xiaoping Mu (Infectious Diseases, 2017)

Effects of light curing modes and ethanol-wet bonding on dentin bonding properties - Mu-zi Li; Jin-rui Wang; Hong Liu; Xia Wang; Kang Gan; Xiu-ju Liu; De-li Niu; Xiao-qing Song (Journal of Zhejiang University-SCIENCE B, 2016)

Characterization of the prokaryotic diversity through a stratigraphic permafrost core profile from the Qinghai-Tibet Plateau - Weigang Hu; Qi Zhang; Tian Tian; Dingyao Li; Gang Cheng; Jing Mu; Qingbai Wu; Fujun Niu; Lizhe An; Huyuan Feng (Extremophiles, 2016)

Proanthocyanidin Protects Human Embryo Hepatocytes from Fluoride-Induced Oxidative Stress by Regulating Iron Metabolism - Qiang Niu; Lati Mu; Shugang Li; Shangzhi Xu; Ruling Ma; Shuxia Guo (Biological Trace Element Research, 2016)

Indoor air pollution and risk of lung cancer among Chinese female non-smokers - Lina Mu; Li Liu; Rungui Niu; Baoxing Zhao; Jianping Shi; Yanli Li; Mya Swanson; William Scheider; Jia Su; Shen-Chih Chang; Shunzhang Yu; Zuo-Feng Zhang (Cancer Causes & Control, 2013)